ANALYSIS OF THE CONTRIBUTION OF PINEAPPLE FARMINGINCOME TO HOUSEHOLD INCOME IN JANGA-JANGAN VILLAGE, PUJANANTING DISTRICT, BARRU REGENCY - Fitriani; Isnam Junais; Hasriani Hasriani (AgriMu, 2026)
This study aims to determine the income of pineapple farming and its contribution to the household income of farmers in Jangan-Jangan Village, Pujananting District, Barru Regency. The research was conducted in November-December 2025 with a descriptive quantitative method and a sample of 25 farmers selected by simple random sampling. The results of the study show that the average net income of pineapple farming is IDR 8,936,797/month, with an income of IDR 12,209,000/month and production costs of IDR 3,272,203/month. Additional income from other activities averages IDR 1,560,000/month, so that the total household income reaches IDR 10,496,797/month. The contribution of pineapple farming to household income is 65% and is relatively high, so it plays an important role in improving the welfare of farmers.